Perancangan Tempat Sampah Anorganik Secara Otomatis Menggunakan Sensor Ultrasonik dan Arduino Uno - Rima Tamara Aldisa; Mohammad Aldinugroho Abdullah; Andilaw Andilaw (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
Inorganic waste is waste that cannot be decomposed, in the laboratory a trash can has been provided, but there are still many laboratory users who still put, leave waste such as used paper and plastic bottles in any place. can help in facilitating laboratory users in disposing of waste only by using sensors, so a tool is designed that can be easily affordable and easy to use to prevent the amount of waste and piles of waste paper and plastic bottles. The author designed the Design of Automatic Inorganic Garbage Disposal Using Ultrasonic Sensors and Arduino Uno Case Study: Unas Artificial Intelligence Laboratory by using our hand proximity sensor the trash can opens automatically, we don't need to hold or touch the trash can, just use the proximity sensor, it opens automatically, and the trash can will close automatically if the proximity sensor moves away. So the author wants to design and make this tool that can be very helpful for use in the laboratory in order to minimize the amount of inorganic waste left behind.